Conditional Moment Closure Modelling of a Lifted H2/N2 Turbulent Jet Flame Using the Presumed Mapping Function Approach. (15th June 2015) - El Sayed, Ahmad; Fraser, Roydon A.
Abstract : A lifted hydrogen/nitrogen turbulent jet flame issuing into a vitiated coflow is investigated using the conditional moment closure (CMC) supplemented by the presumed mapping function (PMF) approach for the modelling of conditional mixing and velocity statistics. Using a prescribed reference field, the PMF approach yields a presumed probability density function (PDF) for the mixture fraction, which is then used in closing the conditional scalar dissipation rate (CSDR) and conditional velocity in a fully consistent manner. These closures are applied to a lifted flame and the findings are compared to previous results obtained using β -PDF-based closures over a range of coflow temperatures (T c ). The PMF results are in line with those of the β -PDF and compare well to measurements. The transport budgets in mixture fraction and physical spaces and the radical history ahead of the stabilisation height indicate that the stabilisation mechanism is susceptible to T c . As in the previous β -PDF calculations, autoignition around the "most reactive" mixture fraction remains the controlling mechanism for sufficiently high T c . Departure from the β -PDF predictions is observed when T c is decreased as PMF predicts stabilisation by means of premixed flame propagation. This conclusion is based on the observation that lean mixtures are heated by downstream burning mixtures in a preheat zone developing ahead of the stabilization height. The spurious sources, which stem from inconsistent CSDR modelling, are further investigated. The findings reveal that their effect is small but nonnegligible, most notably within the flame zone.